Learning by example : imitation and innovation at a global bank - Strang, David (Princeton University Press, 2010)
In business, as in other aspects of life, we learn and grow from the examples set by others. Imitation can lead to innovation. But in order to grow innovatively, how do businesses decide what firms to imitate? And how do they choose what practices to follow? Learning by Example takes an unprecedented look at the benchmarking initiative of a major financial institution. David Strang closely follows twenty-one teams of managers sent out to observe the practices of other companies in order to develop recommendations for change in their own organization. Through extensive interviews, surveys, and.